MANFAAT GOODWILL IMPAIRMENT, EARNINGS PER SHARE (EPS), SERTA KANDUNGAN GOODWILL IMPAIRMENT PADA EARNINGS PER SHARE TERHADAP HARGA SAHAM - Dheni Indra Kusuma (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
Abstract The development of science and the rules that apply internationally demanded radical changes in every part that receives the impact of the rule changes. Goodwill is one part that is still busy discussed at this time. Change of rules recognition of the amortization of goodwill to be a rule that only recognizes Goodwill Impairment on the financial statements give a separate impact to the financial statements presented. Investors can assume both positive and negative on the financial statements are presented so that it will affect the company's stock price on the Indonesia Stock Exchange.This study aimed to examine the effect of Goodwill Impairment on stock prices, also conducted to examine the effect of earnings per share which has taken into account the value of Goodwill Impairment on stock prices, and testing the effect of variable Goodwill Impairment issued separately from EPS on stock prices.Hypothesis testing is done by using a cross-sectional regressions for each year of observations from the years 2011-2015 and the whole year of observation (pooled regression). This study uses data observed company selected by purposive sampling the years 2011-2015 of all companies listed on the Indonesia Stock Exchange reported that generate goodwill and positive earnings. We find that goodwill impairment does not explain significantly more of the observed distribution of share price. Our result suggests that goodwill impairment does not contain incremental value-relevant information. Keywords: earnings per share (EPS), goodwill amortization, goodwill impairment, Indonesia Stock Exchange, stock price